Prognostic nutritional index predicts prognosis in patients with metastatic nasopharyngeal carcinoma - Wei, Gan-Bao (Onco Targets Ther, 2016)
OBJECTIVE: This study aimed to investigate the prognostic value of Onodera’s prognostic nutritional index (PNI) in patients with metastatic nasopharyngeal carcinoma (NPC). METHODS: A total of 187 patients with metastatic NPC treated with cisplatin-based chemotherapy were retrospectively reviewed. The PNI was calculated using the following formula: serum albumin level (gram per liter) +0.005× peripheral lymphocyte count (per cubic millimeter). A receiver operating characteristics curve for overall survival (OS) with the highest Youden index was determined to calculate the best cutoff value of PNI. The relationship between PNI and clinicopathological parameters was compared with the χ(2) test. Survival analysis was applied to evaluate the predictive value of PNI. RESULTS: The median PNI in this study was 49.0 (ranging from 32.2 to 78.4). The best cutoff value of PNI for OS was 51.0 according to the receiver operating characteristics analysis. The median OS time was 13.0 months. The multivariate analysis indicated that the complete response (hazard ratio 0.681, 95% confidence interval 0.574–0.902; P=0.013) and PNI (hazard ratio 1.732, 95% confidence interval 1.216–2.892; P=0.005) were independent prognostic factors for OS in patients with metastatic NPC. CONCLUSION: This study revealed that PNI is a simple and effective predictor for overall survival in patients with metastatic NPC.